Plant and microbial strategies to improve the phosphorus efficiency of agriculture - Richardson, Alan E.; Lynch, Jonathan P.; Ryan, Peter R.; Delhaize, Emmanuel; Smith, F. Andrew; Smith, Sally E.; Harvey, Paul R.; Ryan, Megan H.; Veneklaas, Erik J.; Lambers, Hans; Oberson, Astrid; Culvenor, Richard A.; et al. (Plant and soil, 2011)
Background Agricultural production is often limited by low phosphorus (P) availability. In developing countries, which have limited access to P fertiliser, there is a need to develop plants that are more efficient at low soil P. In fertilised and intensive systems, P-efficient plants are required to minimise inefficient use of P-inputs and to reduce potential for loss of P to the environment. Scope Three strategies by which plants and microorganisms may improve P-use efficiency are outlined: (i) Root-foraging strategies that improve P acquisition by lowering the critical P requirement of plant growth and allowing agriculture to operate at lower levels of soil P; (ii) P-mining strategies to enhance the desorption, solubilisation or mineralisation of P from sparingly-available sources in soil using root exudates (organic anions, phosphatases), and (iii) improving internal P-utilisation efficiency through the use of plants that yield more per unit of P uptake. Conclusions We critically review evidence that more P-efficient plants can be developed by modifying root growth and architecture, through manipulation of root exudates or by managing plant-microbial associations such as arbuscular mycorrhizal fungi and microbial inoculants. Opportunities to develop P-efficient plants through breeding or genetic modification are described and issues that may limit success including potential trade-offs and trait interactions are discussed. Whilst demonstrable progress has been made by selecting plants for root morphological traits, the potential for manipulating root physiological traits or selecting plants for low internal P concentration has yet to be realised.